Improved Methods for Deamination-Based m6A Detection - Zhu, Huanyu; Yin, Xinhe; Holley, Christopher L.; Meyer, Kate D. (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) is a critical regulator of gene expression and cellular function. Much of our knowledge of m6A has been enabled by the identification of m6A sites transcriptome-wide. However, global m6A profiling methods require high amounts of input RNA to accurately identify methylated RNAs, making m6A profiling from rare cell types or scarce tissue samples infeasible. To overcome this issue, we previously developed DART-seq, which relies on the expression of a fusion protein consisting of the APOBEC1 cytidine deaminase tethered to the m6A-binding YTH domain. APOBEC1-YTH directs C-to-U mutations adjacent to m6A sites, therefore enabling single nucleotide-resolution m6A mapping. Here, we present an improved version of DART-seq which utilizes a variant of the YTH domain engineered to achieve enhanced m6A recognition. In addition, we develop in vitro DART-seq and show that it performs similarly to cellular DART-seq and can map m6A in any sample of interest using nanogram amounts of total RNA. Altogether, these improvements to the DART-seq approach will enable better m6A detection and will facilitate the mapping of m6A in samples not previously amenable to global m6A profiling.